Analysis on chemical and physical properties of dried sago bagasse - Nur Tantiyani Ali Othman; Nur Izzati Husna Ahmad Nadzri; Masli Irwan Rosli (Penerbit Universiti Kebangsaan Malaysia, 2024)
The uncontrollable of sago bagasse waste from sago industry production become an environmental issue as it just dumping directly into nearby rivers which can affect a river pollution if not treated well. As it still has about 70% starch content, it has a potential to be converted to the others value-added product such as animal feed. However, before it can be converted to others product, it should go through a drying process to reduce its higher moisture content (90 wt.%), as well to prevent any micro bacteria growth and for long lasting packaging. Thus, this study focused on the evaluation of drying process at T=70 and 80 °C on reducing of its final moisture content by using three drying approaches: fluidized bed dryer (FBD), micro-oven and direct sunlight drying. Then, these samples of dried sago were analysed to determine its properties of starch, fibre, and ash, as well to study its functional organic chemical group by using Fourier infrared transform (FTIR) method. The results show the reduction of sago water content by FBD shown a significant result as compared to others drying methods as the FBD method produces a good solid mixed between particles. Besides, the drying rate using the FBD was achieved in a shorter time within 30 min as compared to oven which within 2 hours and sunlight drying within 6 days to achieve similar final desired moisture content at 11 wt.%. The analysis on the starch properties using the FBD was also almost 75% more higher than oven, which is about 70% starch content. Moreover, the presence of starch was successful proven by the presence of acrylic acid at a wavelength of 1539.72 cm-1 for FBD sample by using FTIR. In addition, using the FBD, the sago waste can maintain its quality as an animal feed by reached a brightness level, W1 as compared to the slurry sago waste where the dried sago using FBD is 58.78%, meanwhile the fresh slurry sago waste is 93.31%. In conclusion, the sago drying in the FBD at T=80 °C was selected as the optimum drying condition as it had achieved a short drying rate for desired final 11 wt.% moisture content and resulted in better on the chemical and physical analysis.